2010
DOI: 10.1080/02705060.2010.9664407
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Copper on a Lotic Benthic Invertebrate Community: Response and Recovery

Abstract: We examined the impact of copper on invertebrate community composition in a small stream (Pelican Brook) originating from a zebra mussel infested lake in central Minnesota. One bay of the lake was treated weekly with chelated copper during the summers of 2004 and 2005, resulting in copper levels in Pelican Brook ranging from 0.1 to 0.8 mg/L for three months each summer. Benthic macroinvertebrates were collected from two sites in Pelican Brook in spring and fall over four years (2004)(2005)(2006)(2007), includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…For example, Tanypodinae were negatively affected by copper [14]; in the present study, however, no effect of copper was identified. Other studies that have considered the effects of copper on Tanypodinae in the field have also found species within the subfamily to be copper tolerant, which supports the lack of response in the present study [32,33]. There was also interspecies variation in copper susceptibility of Ostracoda within the present study, as 1 species of benthic Ostracoda was not affected by copper but another declined in abundance.…”
Section: The Importance Of Interspecies Variation In Sensitivitysupporting
confidence: 88%
See 1 more Smart Citation
“…For example, Tanypodinae were negatively affected by copper [14]; in the present study, however, no effect of copper was identified. Other studies that have considered the effects of copper on Tanypodinae in the field have also found species within the subfamily to be copper tolerant, which supports the lack of response in the present study [32,33]. There was also interspecies variation in copper susceptibility of Ostracoda within the present study, as 1 species of benthic Ostracoda was not affected by copper but another declined in abundance.…”
Section: The Importance Of Interspecies Variation In Sensitivitysupporting
confidence: 88%
“…The effect of time on the total abundance of invertebrates in the water column was significant (F 8,120 ¼ 59, p < 0.001). However, there was no significant effect of treatment (F 4,15 ¼ 1, p ¼ 0.44) on total abundance, nor was there a significant interaction between time and treatment (F 32,120…”
Section: Water Column Community Responsementioning
confidence: 92%